A three month old infant with severe respiratory distress - Ahmed, Zainab; Sadiq, Sara; Quraishi, Shifa; Mirza, Sadiq (Journal of the Pakistan Medical Association, 2024)
This case report discusses the diagnostic challenge of congenital lobar emphysema (CLE) in a three-month old infant with severe respiratory distress. The infant was initially misdiagnosed and managed as a case of pneumothorax. This case highlights the importance of CT scans as a diagnostic tool for early diagnosis and lifesaving management of CLE. It also signifies the need for adequate funds and infrastructure in the health care system especially in rural areas of developing countries like Pakistan. Keywords: Congenital lobar emphysema, respiratory distress, CT scan.